Study on the Potential of Forest Areas in Aspects of Land Fertility In Wonosalam District, Jombang Regency - Maroeto; Rossyda Priyadarshini; Siswanto; Mohammad Idhom; Wahyu Santoso (Nusantara Science and Technology Proceedings, 2021)
Forests are one of the natural resources of high value for human benefit, both direct and indirect benefits. The management of forest resources does not date from the legal basis of Article 6 of Law no. 41 of 1999 (regarding Forestry) which states that natural resource management efforts in forest areas are carried out through protection, conservation and production functions by taking into account the continuity of their supply and the surrounding environment. UPN "Veteran" East Java as a State University in East Java proposes the Forest Area program with Special Purposes (KHDTK) as an effort to develop education and research as well as community service. The purpose of this research is to map forest areas based on fertility characteristics and land availability suitable for the development of KHDTK Wonosalam. The results of the research can be seen that 1. the forest area is based on the interrelation of land evaluation parameters on the distribution of forest land, the limiting factor for water availability in land use units 1, 2, and has primary obstacles in the dry season, resulting in drought and inappropriate land use. with its designation on land prone to erosion. Plants that dominate the forest area are annual plant species, including pine, clove and mahogany, while intercropping consists of coffee, banana and corn. Aspects of land fertility holistically have inhibiting factors, namely the low levels of elements C - Organic, available P and K2O. 2. Efforts to conserve land as an option for forest land management before the decline in land quality occurs by making irrigation and drainage channels to avoid water drought, applying organic fertilizers and selecting plants physiologically according to the characteristics of forest land. In addition, it is hoped that there will be an increase in water availability and land productivity by applying the principles of sustainable agriculture.